Two new species of Paramphimonhystrella (Nematoda, Monhysterida, Xyalidae) from the deep-sea sediments in the Western Pacific Ocean and adjacent shelf seafloor - Shi, Benze; Yu, Tingting; Xu, Kuidong (Zootaxa, 2017)
Two new species of marine nematodes, Paramphimonhystrella longispicula sp. n. in the deep-sea sediments from the Philippine Sea in the tropical Western Pacific Ocean with the water depth of 3920–5176 m and P. eurystoma sp. n. in the shelf seafloor from the East China Sea with the water depth of 55–64 m, are described. Both species possess long and slender spicules, which are present only in the congener P. barbula, a species discovered from the continental slope of New Zealand. Paramphimonhystrella longispicula sp. n. can be easily distinguished from P. barbula by the relatively broader buccal cavity, the unequally long cervical setae and a higher number of terminal setae. Paramphimonhystrella eurystoma sp. n. is unique in having a peculiar gubernaculum with two proximal capitula and a peculiar hammer-shaped cuticularized piece posterior to vulva, by which it can be distinguished from P. longispicula sp. n. and P. barbula as well as other congeners. Paramphimonhystrella longispicula sp. n. differs from P. eurystoma sp. n. also by the number of terminal setae (4 vs. 2). A dichotomous key to nine valid species of Paramphimonhystrella is provided.